Evaluasi Waktu Tunggu Pelayanan Resep Elektronik Pada Pasien Rawat Jalan Di RSUD Kraton Kab. Pekalongan (VitaMedica : Jurnal Rumpun Kesehatan Umum, 2026)
Prescription service wait times are an indicator of pharmacy service quality that directly impacts patient satisfaction and the Hospital Minimum Service Standards (SPM). The Kraton Regional General Hospital in Pekalongan Regency has implemented an electronic prescribing system (e-prescribing) to improve efficiency and reduce prescribing errors. However, with prescription volumes reaching hundreds per day, periodic evaluation is necessary to ensure that services remain in compliance with standards. This study aims to evaluate the waiting time for electronic prescription services among outpatients at the Pharmacy Department of RSUD Kraton, Pekalongan Regency, and to compare it with the Ministry of Health’s standards. This is a descriptive observational study using a quantitative approach. The study sample consisted of 300 prescriptions (74 compounded prescriptions and 226 non-compounded prescriptions) selected via simple random sampling from medical records for the period August–October 2025. Research instruments included an observation sheet and an interview guide to support observational data. Data analysis was conducted descriptively to calculate the average service waiting time. The results showed that the average service time for non-compounded prescriptions was 7 minutes and 42 seconds, while for compounded prescriptions it reached 28 minutes and 11 seconds. All samples examined met the established waiting time standards, namely ≤30 minutes for non-compounded prescriptions and ≤60 minutes for compounded prescriptions, in accordance with Ministry of Health Regulation No. 4 of 2019 and Ministry of Health Decree No. 129/2008. The electronic prescription service at Kraton District General Hospital in Pekalongan Regency has been operating very efficiently and meets the Minimum Service Standards (SPM). The implementation of e-prescribing technology has significantly contributed to maintaining the speed and quality of pharmaceutical services on an ongoing basis.